Recent decades are the warmest in over 400 years in Northeast Asia: evidence from tree-ring anatomy - Nela Altmanová; Georg von Arx; Jiří Doležal; Pavel Fibich; Toshihiko Hara; Jan Altman (Climatic Change, 2026)
Recent rapid climate warming often exceeds the rate and magnitude of pre-industrial variability over the Common Era. While contemporary warming exhibits a high degree of global synchrony, pre-industrial warm and cold periods were often spatially heterogeneous and asynchronous. Consequently, reliable regional paleoclimate records remain essential for understanding past climate variability. Here, we present an annually resolved, 411-year-long reconstruction of June 9–July 30 minimum temperature based on cell wall thickness of Picea glehnii trees from Hokkaido, Japan. Our reconstruction, developed from non-detrended chronologies and daily climate data ( r = -0.68, p < 0.05), provides a spectrally unbiased record of temperature variability across Northeast Asia. It captures pronounced cold and warm periods that align with historical records and regional climate reconstructions. For instance, it reveals cold periods in the 17th century corresponding to the Maunder Minimum and a distinct cold period in the 1830s, which coincided with one of the severest famines in Japanese history. Crucially, the period from 1994 to 2016 was the longest warm period in the entire reconstruction. The reconstruction also shows significant, persistent multidecadal variability that likely reflects the Pacific Decadal Oscillation. These findings highlight the strong potential of quantitative wood anatomy to improve our understanding of long-term climate dynamics and, thus, reduce uncertainties in future climate projections.